(untitled) (2017)
Hydroxyapatite (HAp) was obtained from tilapia scales by two extractionmethods: direct calcination and acid-base treatment. The physicochemicalcharacteristics of the obtained HAps were evaluated by thermogravimetricanalysis, X-ray fluorescence, X-ray diffraction, scanning electron microscopy, surface area, infrared spectroscopy, and basicity measurement at 298 K by CO2-pulse titration. Furthermore, the CO2 capture capacity of the solids at high temperature was also determined. Both methods showed the presence of a HAp phase although significant differences in the properties of the solids were found. The HAp obtained by direct calcination, exhibited a lower crystallinity and a greater surface area and basicity than the HAp obtained by the acid-base treatment. These features were correlated with the solid’s CO2 capture capacity. In this work, CO2 capture capacity values for HAp yielded by calcination ranged from 2.5 to 3.2 mg CO2 /g captured at 973 K, and for the acid-base treatment-derived HAp, CO2 capture capacity values between 1.2 to 2.5 mg CO2 /g were recorded. These results reveal the potential of HAps extracted from tilapia scales as solids with high CO2 capture capacity, thermal stability, and capture/release cycles reversibility.